Single-shot emittance measurement of a 508MeV electron beam using the pepper-pot method - Delerue, N; Bartolini, R; Doucas, G; Lau, P; Peach, K; Reichold, A; Senanayake, R; Urner, D (Joint Accelerator Conferences Website (JACoW), 2010)
We describe a method that uses a modified pepper-pot design to measure in a single shot the emittance of electron beams with energies above 100 MeV. Our setup consists of several thin layers of tantalum with spacers in between to leave slits through which the electron beam can be sampled. We report on a measurement done using this method at the DAFNE BTF with a 508 MeV electron beam.